Classification of Personality based on Beauty Product Reviews Using the TF-IDF and Naïve Bayes (Case Study : Female Daily) - Novia Russelia Wassi; Adiwijaya Adiwijaya; Mahendra Dwifebri Purbolaksono (Telkom University, 2020)
A person's personality is an important parameter to determine the character of each person and also as an assessment in various ways. In this day and age personality can not only be known from psychological tests, but also can be known in various ways. One way is through reviews presented in electronic media. In this study, a person's personality was classified into three